Depression and Anxiety in Patients with Chronic Renal Failure: The Effect of Sociodemographic Characteristics - Paraskevi Theofilou (International Journal of Nephrology)
“Do the sociodemographic characteristics relate to the levels of depression and anxiety in patients with chronic renal failure in Athens?” The study investigated in a group of renal disease patients differences referring to self-reported mental health, depression, and anxiety, after controlling for gender, age, education, and marital status. Patient-reported assessments included General Health Questionnaire (GHQ-28) of Goldberg, Center for Epidemiological Studies Depression Scale (CES-D), and State-Trait Anxiety Inventory (STAI I & II) of Spielberger. Female patients reported higher scores in the trait anxiety measure. Elder patients reported higher scores in the GHQ-28 subscale of social dysfunction and in the CES-D depression scale, while less educated patients presented higher scores in the GHQ-28 subscales of anxiety/insomnia and severe depression. Divorced/widowed patients presented higher scores in the severe depression subscale. Findings provide evidence that sociodemographic variables, like being older, less educated, and divorced/widowed, relate to a more compromised mental health.